1993
DOI: 10.1056/nejm199304153281504
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cardiac Pacing with Drug Therapy in the Treatment of Neurocardiogenic (Vasovagal) Syncope with Bradycardia or Asystole

Abstract: In patients with neurocardiogenic syncope associated with bradycardia or asystole, drug therapy is often effective in preventing syncope, whereas artificial pacing is not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0
3

Year Published

1997
1997
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(77 citation statements)
references
References 21 publications
3
71
0
3
Order By: Relevance
“…Finally, the presence of either reduced or increased MSNA in subjects with syncope may also explain the dissimilar therapeutic response observed in different populations (50,51). Conceivably, patients in whom syncope is associated with a blunted increase in sympathetic tone would benefit from ␣-adrenergic receptor agonists or from agents that increase sympathetic tone.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the presence of either reduced or increased MSNA in subjects with syncope may also explain the dissimilar therapeutic response observed in different populations (50,51). Conceivably, patients in whom syncope is associated with a blunted increase in sympathetic tone would benefit from ␣-adrenergic receptor agonists or from agents that increase sympathetic tone.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, 2 recent publications claim success in treating humans for vasodepressor reactions with theophylline. 16,17 Earlier studies showed that the paradoxic bradycardia in this rat model depends on cardiac vagal afferents: it is blocked by cervical vagotomy or intrapericardial lidocaine but is independent of efferent vagal tone because it is unaffected by muscarinic receptor blockade with atropine. 6,7 Similarly, the paradoxic bradycardia response to inferior vena cava occlusion during isoproterenol and dipyridamole was not affected by pretreatment with atropine, but it was blocked by cervical vagotomy.…”
Section: Discussionmentioning
confidence: 85%
“…28 Sra et al studied 22 patients by tilting test with temporary pacing. 17 Although they concluded that artificial pacing at a rate 20% higher than the basic HR could not prevent vasovagal syncope, the reduction of arterial blood pressure was significantly less during the pacing study. Furthermore, only 5 patients developed syncopes during tilting test with pacing compared with 18 patients who fainted during baseline tilt test without pacing.…”
Section: Discussionmentioning
confidence: 96%
“…5,6,15 It has been shown that vasovagal attacks could not be aborted by administration of atropine 15,16 or by artificial pacing. 16,17 Confronted with these diverse results, it appears appropriate to reassess the hemodynamic differences between patients who do and do not develop bradycardia during vasovagal/ vasodepressor syncope.…”
Section: Introductionmentioning
confidence: 99%